2005
DOI: 10.1080/07315724.2005.10719497
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Eggs on Satiety in Overweight and Obese Subjects

Abstract: Compared to an isocaloric, equal weight bagel-based breakfast, the egg-breakfast induced greater satiety and significantly reduced short-term food intake. The potential role of a routine egg breakfast in producing a sustained caloric deficit and consequent weight loss, should be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 19 publications
4
54
1
Order By: Relevance
“…Another interesting healthful attribute of eggs is their ability to suppress appetite [46]. A recent study compared two different breakfasts, a bagelbased and an egg-based breakfast in a crossover design in male participants [47 & ].…”
Section: Eggs and Dietary Cholesterolmentioning
confidence: 99%
“…Another interesting healthful attribute of eggs is their ability to suppress appetite [46]. A recent study compared two different breakfasts, a bagelbased and an egg-based breakfast in a crossover design in male participants [47 & ].…”
Section: Eggs and Dietary Cholesterolmentioning
confidence: 99%
“…The amino acid profile of egg protein (approximately 6·5 g/egg) is similar to that of beef steak, but has greater bioavailability, as indicated by its higher protein digestibility corrected amino acid score (egg 118, beef steak 92, milk 121, soya 9, wheat 42) (21) . Dietary protein has long been associated with increased satiety, and there is evidence to suggest that the high protein content of eggs may contribute to this effect (22,23) . Eggs have also been shown to promote weight loss in overweight and obese subjects by increasing feelings of satiety and reducing short-term energy intake (24) .…”
Section: Egg: Nutrient Compositionmentioning
confidence: 99%
“…Research over the past decade has shown no correlation between cholesterol consumption and risk of coronary heart disease or stroke, and this is no longer considered to be a causative factor in coronary heart disease through its association with serum cholesterol (Hu et al 1999, Nakamura et al 2006, Gray and Griffin 2009. In relation to satiety, consumption of eggs at breakfast has previously been shown to correlate with greater satiety scores and reduction of short-term energy intake (Holt et al 1995, Vander Wal et al 2005, Ratliff et al 2010. Although the effects of eggs consumed at breakfast on satiety have been investigated, equivalent studies investigating consumption at lunch have not been conducted.…”
Section: Introductionmentioning
confidence: 94%